PERUBAHAN TATA GUNA LAHAN TERHADAP PARAMETER Cp DAN Ct HSS SNYDER PADA DAERAH ALIRAN SUNGAI SANGAT KECIL (DAS CODE) - Barid, Burhan; Wahyuni, Sri; Lesmana, Surya Budi (Direktorat Bina Teknik Sumber Daya Air, Kementerian Pekerjaan Umum dan Perumahan Rakyat, 2024)
The growth in population over time requires improvements in infrastructure services, which often lead to changes in land use within watersheds. These changes frequently result in the ground surface becoming more impervious, ultimately increasing runoff discharge. Land use changes have a significant impact on the Cp and Ct parameters within watersheds. To assess the impact of land use changes, we conducted research using the Snyder Synthetic Unit Hydrograph (SUH) Method on the Code Watershed in 2016 and 2020. Determining the Ct and Cp parameters is essential in predicting peak discharge. Cp is a characteristic watershed parameter that naturally changes as the watershed itself changes, while Ct is a parameter related to watershed slope, which also varies with changes in land use. The analysis shows an increase in the values of both parameters over the two different time periods, leading to an increase in peak discharge. In 2016, Cp and Ct values were 0.40 and 1.80, respectively, with a peak discharge of 0.47 m³/s. By 2020, these values had risen to 0.60 and 1.85, with a peak discharge of 0.68 m³/s. The increase in the Cp parameter indicates that the Code Watershed has become more impervious, reflecting a change in its characteristics. Similarly, the increase in the Ct parameter indicates changes in the watershed slope due to land use constraints. The RMSE calculation results show that the SUH Snyder prediction is consistent with the unit hydrograph calculations.Keywords: land use, discharge, Cp , Ct , SUH Snyder